Analyza Legal Protection of Copyright to the Creator of Books By Law Number 28 Year 2014 on Copyright in Medan - Dina Andiza (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
A Books as protected creations have been regulated in Article 40 paragraph or sub-paragraph an of Copyright Act no. The UUHC has arranged for the recording of the work in Article 64, so that the creator may record his book creation to the Director General of HAKI in Jakarta or through the Provincial Dept. of Regional Officers (as an extension of the registration process in the region). A Based on the Decree of the Minister of Justice of the Republic of Indonesia Number M.09-PR.07.06 of 1999, the person whose name as registered in the Regional Office of the Ministry of Law and Human Rights as considered as the creator (centralized system), which can facilitate proofs in case of dispute. This study aims to find out why the creators of the book do not record his creation and the barriers to register his production and the protection of copyright law on book creation gave the Copyright Act No. 28 of 2014.In this research an conducted by using descriptive qualitative research model and information will be an extracted from various data sources and types of data sources that will utilize in this research, including secondary data related to Copyright, legislation, scientific journals, papers and others. Primary Law Material in this research consists of UUHC 2014, Government Regulation, Ministerial Decree and Ministerial Regulation. Secondary Law Material comprises of literature books related to Copyright. The Tertiary Law material comprises of the Great Indonesian Dictionary. An output of scientific publication in the form of writing in Journal of Abdi Ilmu which has ISSN, obtained the level of understanding on the protection of Copyright law on the book's creation regarding Law no. 28 of 2014 on Copyright.